Evaluación de un inhibidor de incrustación para evitar taponamiento de las líneas de producción en una plataforma petrolera (2018)
This project addresses one of the most frequent problems presented by the oil industry in the process of crude production; this is the appearance of scale that is formed by the reaction of the ions present in the formation water; the growth of the incrustations results from the homogeneous and heterogeneous nucleation processes that occur in parallel, and are deposited in the production pipes, causing, among others, plugging in them. In this work the formation of scale in the oil platform located in Brazil as a cause of the secondary recovery by injection of seawater from the beginning of the production was studied to guarantee the maximum production of oil that brings about reduction and increase in costs of oil. maintenance in the extraction and production of hydrocarbons in the maritime oil platform, being one of the main problems to be mitigated and prevented by the operating companies.